Synthesis and Biological Activities of Some Metal Complexes of 2-Thiouracil and Its Derivatives: A Review - Petja Emilova Marinova; Kristina Dimova Tamahkyarova (Compounds, 2024)
The thionamide antithyroid agents were discovered largely through observations carried out by various researchers in the 1940s that found that sulfhydryl-containing substances were goitrogenic in animals. Prof. Edwin B. Astwood started using these drugs to treat hyperthyroidism. In the current paper, we summarize the development background of these agents and the coordination possibility of 2-thiouracil and its derivatives, as well as the biological activities of some of its complexes. Some of them are used as agents for the treatment of tuberculosis, and arthritis, others have bactericidal and fungicidal activity, the third cytotoxic properties, and could be used to treat various types of cancer.